A inserção profissional e a atuação docente na Educação Infantil - Oliveira, Midiã Olinto de (2018)
This research investigated the insertion period of beginner teachers in nursery education in a municipal school of Guarulhos, with focus on the analysis of pedagogical activities proposed, reflecting on possible contributions and limitations of professional education. Besides that, difficulties faced by inexperienced teachers and their objective work conditions are described and analyzed. The main hypothesis is that teachers’ practices is oriented by a habitus composed of dispositions that allow the mobilization of different knowledge to promote learning and development of children. The research data were obtained during 2016, by questionnaires, semi-structured interviews and observing the performance of four teachers, two of them experienced and two of them new. For the analysis, historical-cultural theory and its conception of development and of the teacher’s central role in the organization of teaching were adopted. Also Pierre Bourdieu’s concepts of habitus and cultural capital were used. The data analysis pointed to the prevalence of spontaneous and unplanned practices, as well as to formative experiences that reflect social conditions in which the education of small children in the public school occurs. The access to knowledge is poor and there is limited and restricted participation of children in the activities. Furthermore, inexperienced teachers face difficulties related to class management, discipline, mastery of specific contents of this teaching area, relating to peers and parents, as well as coping with precarious working conditions